Upaya Meningkatkan Kompetensi Kepribadian Guru PAI dalam Membentuk Akhlak Peserta Didik di MTs Raden Fatah - Sinta Nur Hilali; Moh.Badrul Alam; Khaerurani Nur Asyifa; Eka Ratna Safitri; Muhammad Miftahussalam; Pindha Kaptiningrum; Saeful Bahri (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2024)
This qualitative research aims to describe in depth how PAI teacher competency influences the moral formation of students at MTs Raden Fatah. Through in-depth interviews PAI teachers a, this research revealed that teachers' personality competencies, especially in terms of warmth, empathy and effective communication, create strong emotional bonds between teachers and students. This bond becomes the basis for the process of internalizing religious values and sustainable moral formation. Students tend to imitate the behavior of teachers who they consider to be ideal and exemplary figures. Apart from that, teachers who have good personality competencies are able to create a safe and comfortable learning environment, so that students feel freer to ask questions, collaborate and develop themselves.